Ion-induced soot nucleation using a new potential for curved aromatics - Bowal, Kimberly (2020)
A potential able to capture the properties and interactions of curved polycyclic aromatic hydrocarbons (cPAHs) was developed and used to investigate the nucleation behavior and structure of nascent soot particles. The flexoelectric charge polarization of cPAHs caused by pentagon integration was included through the introduction of off-site virtual atoms, and enhanced dispersion interaction parameters were fitted. The electric polarization and intermolecular interactions of cPAHs were accurately reproduced compared to ab initio calculations. This potential was used within molecular dynamics simulations to examine the homogeneous and heterogeneous nucleation behavior of the cPAH corannulene and planar PAH coronene across a range of temperatures relevant to combustion. The enhanced interactions between cPAHs and potassium ions resulted in significant and rapid nucleation of stable clusters compared to all other systems, highlighting their importance in soot nucleation. In addition, the resulting cPAH clusters present morphologies distinct from the stacked planar PAH clusters.